ASSESSING THE ENVIRONMENTAL IMPACT OF ROADWAY’S CONSTRUCTION ON ADJACENT WATER RESOURCES: A CASE STUDY OF THE SOUTHERN PART OF ALBANIA - Blerina BEQAJ (Scientific Journal of Silesian University of Technology. Series Transport)
Water is one of nature’s resources. As urbanisation grows, new roadways and highways are constructed for the transport sector and development. Due to roadway infrastructure, the development of the quality of surface water bodies in close proximity to roads is deteriorating and has become a major environmental challenge. Considered as one of the major nonpoint pollution sources, the construction of new roadways can have short and long-term effects on water quality conditions. This study revealed that road construction activities may be responsible for introducing pollutants in nearby water sources, leading to the deterioration of water quality. The roadway expansion activities affect both the surface and groundwater quality. Furthermore, this study was conducted to assess the effects of a road construction project situated in the southern part of Albania, on physic-chemical parameters of surface water by collecting water samples from Skotini stream. The analysed parameters included pH, dissolved oxygen (DO), biological oxygen demand (BOD5), chemical oxygen demand (COD), electrical conductivity (ECw), total dissolved solids (TDS), salinity, nitrites (NO2-), ammonium (NH4+) and total phosphorus (Ptot). The results revealed that all physic-chemical parameters analysed in the laboratory are between the normal standards classifying these waters as very clean. Further surveillance for quality assessment of water sources near roadway’s construction activities is needed. Various best management practices have been developed and implemented to prevent negative environmental impacts in the transport sector and roadway construction activities. Results of the water quality help strengthen the theory that roadway construction projects in the transport sector, using appropriate best management practices, could yield minimal impact on the overall water quality of surrounding water bodies.